A NEW TYPE OF RELATIONS BETWEEN MAJOR COUNTRIESAS A BASIS FOR BILATERAL RELATIONS BETWEEN CHINA AND THE USA - АЛІЄВ, Гамідулла (Київський національний університет імені Т. Шевченка, 2025)
B a c k g r o u n d . The bilateral relationship between the People's Republic of China (PRC) and the United States of America (USA) is one of thekey elements of the modern system of international relations that affect global stability and security. Bilateral relations between the two countrieshave come a long way from direct confrontation in the mid-20th century to gradual engagement and strategic cooperation. From 1949 to 1971,ideological differences and the Cold War defined their policy as hostile, which was manifested in the US non-recognition of China, US support forTaiwan, and military conflicts (the Korean War of 1950-1953). Despite the longstanding confrontation, after 1971, both countries began to adapt theirpolicies to economic and geopolitical challenges, culminating in the establishment of diplomatic relations in 1979. With Xi Jinping coming to powerin 2013, China proposed the concept of a "new type of relations between great powers" aimed at avoiding conflicts and promoting mutually beneficialcooperation with the United States. However, the evolution of bilateral relations between the two countries in the period from 2013 to 2025demonstrates the growth of strategic rivalry, which complicates the implementation of this model. In this regard, there is a need to analyze bilateralrelations between China and the United States through the prism of the security dilemma and assess the impact of the concept of "a new type ofrelations between great powers" on China's foreign policy strategies and the dynamics of Sino-US relations.M e t h o d s . The following methods were used: political analysis, content analysis, historical analysis, and the method of generalization.R e s u l t s . The historical development of Sino-US relations shows clear stages of transformation and evolution. In the period from the mid-20thcentury to 1971, relations can be characterised as confrontational, driven by ideological confrontation and the Cold War. The United States did notrecognise the PRC, supporting Taiwan, and the Korean War intensified hostility due to China's perception of US actions as a threat to its security.From 1971 to 1989, there was a shift to cautious engagement, including ‘ping-pong diplomacy', Nixon's visit in 1972, and the signing of the ShanghaiCommuniqué, which laid the groundwork for normalising relations between China and the United States. In 1979, the United States recognised thePRC as the only legitimate government of China, although the issue of Taiwan remains a cornerstone of bilateral relations and controversy. Theperiod from 1990 to 2008 was characterised by economic interdependence, particularly after China's accession to the WTO in 2001, but politicaltensions between the two countries still persisted. Xi Jinping's 2013 concept of a "new type of relations between major countries" included thefollowing key principles: no conflict, mutual respect, and mutually beneficial cooperation. It was intended to avoid the traditional confrontationbetween the rising (China) and dominant (the United States) powers. However, the implementation of this model has faced challenges: the 2018 tradewar initiated by the United States through ‘Made in China 2025' has revealed economic rivalry and contradictions between China and the UnitedStates, and China's actions in the South China Sea and around Taiwan have increased security tensions in the region. Based on this, the theoreticalanalysis through the security dilemma and Thucydides' trap confirms that China's rise is perceived by the United States as a threat that has a decisiveimpact on bilateral relations between the states.C o n c l u s i o n s . Bilateral relations between China and the United States in the period from 2013 to 2025 demonstrate a transition from anattempt to build a "new type of relations between great powers" to an escalation of strategic rivalry between the states due to the security dilemma.Despite economic interdependence, differences in key strategic issues and interests, economic conflicts (such as trade wars) and security issues(Taiwan and the South China Sea) have complicated the implementation of this concept. In the future, the development of relations between Chinaand the United States will depend on the ability of the states to find a balance between competition and cooperation in order to ensure global stabilityand predictable bilateral cooperation.

Анотація. Дана стаття присвячена аналізу еволюції двосторонніх відносин між Китайською Народною Республікою та Сполученими Штатами Америки в історичній перспективі, з акцентом на трансформацію відносин від конфронтації до стратегічної взаємодії. У дослідженні розглядається концепція «нового типу відносин між великими країнами» як основа для розуміння сучасних китайсько-американських відносин, особливо в контексті дилеми безпеки. У даному дослідженні аналізуються ключові віхи дипломатичної взаємодії, економічної взаємозалежності та геополітичної конкуренції між двома країнами. Також, стаття оцінює вплив концепції «нового типу відносин між великими країнами» на сучасні двосторонні відносини, розглядаються її основні теоретичні засади та практичні наслідки для китайсько-американських відносин.   Abstract. This article analyses the evolution of bilateral relations between the People's Republic of China and the United States of America from a historical perspective, with a focus on the transformation of relations from confrontation to strategic cooperation. The study examines the concept of a ‘new type of great power relationship’ as a basis for understanding contemporary Sino-US relations, especially in the context of the security dilemma. This study analyses the key milestones of diplomatic interaction, economic interdependence and geopolitical competition between the two countries. The article also assesses the impact of the concept of ‘new type of great power relations’ on contemporary bilateral relations, examining its main theoretical foundations and practical implications for Sino-US relations.
НОВИЙ ТИП ВІДНОСИН МІЖ ВЕЛИКИМИ КРАЇНАМИ ЯК ОСНОВА ДВОСТОРОННІХ ВІДНОСИН КНР ТА США
Keywords: Ключові слова: китайсько-американські відносини; дилема безпеки; відносини великих держав; геополітична конкуренція; дипломатична взаємодія; економічна взаємозалежність; міжнародна стабільність.; китайсько-американські відносини; дилема безпеки; відносини великих держав; геополітична конкуренція; дипломатична взаємодія; економічна взаємозалежність; міжнародна стабільність